Analisis Perbedaan Roa pada Industri Otomotif, Kesehatan, dan F&B di Bei Tahun 2022–2024 - Ardianti Rukmana; Ayu Cahya Riani; Nazwa Safira; Nur Aliza Gunawan; Shoofiyah Azizah; Sunita Dasman (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze differences in Return on Assets (ROA) across the automotive, healthcare, and Food & Beverage (F&B) industries listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. The study employs a quantitative method with a comparative approach. The data used consists of secondary data obtained from the companies’ annual financial reports. The research sample consists of 15 companies selected using purposive sampling, with a total of 45 observations over the three-year observation period. Data analysis was performed using a One-Way ANOVA test after meeting the assumptions of normality and homogeneity. The results indicate a significant difference in Return on Assets (ROA) between the Food & Beverage, healthcare, and automotive industries, with a significance level of 0.019 (< 0.05). The results of the Bonferroni Post Hoc test indicate that there is no significant difference in ROA between the Food & Beverage and healthcare industries; however, there is a significant difference between the automotive industry and both of these industries. The Food & Beverage industry has the highest average ROA at 10.56, followed by the healthcare industry at 10.47, while the automotive industry has the lowest average ROA at 7.62. These findings indicate that industry characteristics and post-pandemic economic conditions influence companies’ ability to generate profits from their assets. Therefore, the results of this study can serve as a basis for investors and company management to evaluate financial performance by industry sector.